A framework for lotic macrosystem research. Issue 2 (2nd February 2021) - Thorp, James H.; Dodds, Walter K.; Robbins, Caleb J.; Maasri, Alain; Arsenault, Emily R.; Lutchen, Jackob A.; Tromboni, Flavia; Hayford, Barbara; Pyron, Mark; Mathews, Gregory S.; Schechner, Anne; Chandra, Sudeep
Abstract: We analyze here the nature of research in freshwater macrosystem biology (especially lotic studies) from both conceptual and current research perspectives. The boundaries of permanent and transitional lotic macrosystems from the smallest to largest spatial extents are described. We contrast ecosystem vs. macrosystem research and macroecology vs. macrosystems ecology and provide some examples of representative aquatic macrosystems ecology projects in the USA. We recommend approaches for incorporating certain large‐scale lotic concepts developed over the last 40 yr as the bases for lotic macrosystem studies. Of these, the three most appropriate in chronological order are the River Continuum Concept, the Riverine Ecosystem Synthesis, and the Stream Biome Gradient Concept. Four other concepts would be suitable for testing macrosystem hypotheses after incorporating small to large conceptual or geographic expansions of the models. We suggest future research directions in lotic macrosystem research in areas of climate change and teleconnections among distant organisms and systems and include general recommendations for conducting macrosystem‐level research.